Estabelecimento in vitro, aclimatização e conservação in vitro de Lippia alba (Mill.) N. E. Brown (Verbenaceae) - Santos, Verônica Araújo (2010)
This study analyzed in vitro establishment, acclimatization and conservation of Lippia alba (Mill.) N. E. Brown. For this purpose, the effect of different concentrations and dipping times of sodium hypochloride in sterile explants was tested. Nodal segments were immersed in sodium hypochloride at different concentrations (0.4, 0.6, 0.8 and 1.0%) and different times (8, 12 and 16 min). After 30 days of incubation bacterial contamination (%), number of shoots, number of leaves and survival (%) were evaluated. The concentration of 1% sodium hypochloride was more effective in controlling contamination. Also the effect of the antibiotic cefotaxime sodium incorporated into the MS medium, to avoid contamination, was tested. Nodal segments were inoculated on MS medium containing different doses of cefotaxime sodium (0, 50, 100, 150 and 200 mg L-1) and 30 days later were evaluated for bacterial contamination (%), oxidation (%) and survival (%). The dose of 200 mg L-1 cefotaxime completely avoided contamination. Shoot tips of Lippia alba were established in vitro on MS medium supplemented with different concentrations of BAP (0, 0.5, 1.0, 1.5 mg L-1). Contamination (%), survival (%), oxidation (%) and the number of shoots were evaluated after 140 days growth. The best result was obtained with 1.5 mg L-1 of BAP. For acclimatization, four types of substrates were tested: Powder coconut + lime (1g L- 1), Plantmax ® + lime (1g L-1), vermiculite + lime (1g L-1) and coconut powder + Plantmax ® +vermiculite (1:1:1) + lime (1g L-1). Survival (%),shoot length (cm), root length (cm), fresh weight of shoot and root (g) and dry weight of shoot and root (g) were evaluated The best result was obtained when using the substrate Plantmax ®. In order to establish a germplasm bank of the species, nodal segments were isolated from in vitro grown seedlings and inoculated in different culture media: T1 (MS + 2% sucrose + 4% sorbitol), T2 (MS + 2% sucrose + 4% sorbitol + 2 mg L-1 calcium pantothenate), T3 (MS + 2% sucrose + 3% mannitol + 2 mg L-1 calcium pantothenate), T4 (MS / 2 + 2% sucrose + 4% sorbitol); T5 (MS / 2 + 2% sucrose + 4% sorbitol + 2 mg L-1 calcium pantothenate) and T6 (MS / 2 + 2% sucrose + 3% mannitol + 2 mg L-1 calcium pantothenate) with 4 replicates, each one consisting of five test tubes with one plant each. Survival (%), explants with shoots (%), number of shoots, root number and height of shoots, were evaluated at 45, 60, 75 and 90 days after inoculation. The medium T6 (MS / 2 + 2% sucrose + 3% mannitol + 2 mgL-1 calcium pantothenate) was the most suitable for in vitro conservation of Lippia alba.